Development of Module and Augmented Reality Based Android Aplication Computer Assembly For Vocational High School Student - Muhammad Ardan Maulana; Yudianto Sujana; Aris Budianto (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
Based on observation in class X TKJ SMK Negeri 1 Sawit. Students had some problem when learning computer assembly. That happens because lack of equipment and learning media. They need a learning media that can be used to study computer assembly not only inside a school but outside as well. We propose to solve that problem with developing a new learning media that can help students learn independently. We develop a module and android based augmented reality application called ARRAKOM . when ARRAKOM detect a marker in the module. It can display a 3-dimensional model in real time. Learning media is created using ADDIE consist of Analysis, Design, Development, Implementation, and Evaluation. In the development stage, we are using an incremental model and created 2 prototypes of ARRAKOM. In result of the feasibility test, Arrakom gets measured with a Likert scale from expert media get percentage 75% very good, 25% good, 0% bad, 0% very bad. for expert material get percentage 57% very good, 43% good, 0% bad, 0% very bad. And from user get percentage 47% very good, 43% good, 3% bad and 0% very bad.